Exploring the Clinical Utility of Cardiorespiratory Optimal Point in Heart Failure Patients: Creating a New Research Gap - Weder A. Silva; Alberto Souza Sá Filho; Plinio S. Ramos; Adriana M. Güntzel Chiappa; Vicente Aprigliano; Iransé Oliveira-Silva; Raphael Martins Cunha; James Oluwagbamigbe Fajemiroye; Rodolfo P. Vieira; Gerson Ferrari; Gaspar R. Chiappa (Applied Sciences)
The cardiorespiratory optimal point (COP) is an emerging submaximal parameter from cardiopulmonary exercise testing (CPET) that reflects the optimal balance between cardiac workload and pulmonary ventilation. Recent studies have explored the clinical utility and prognostic value of the COP in various populations, particularly in patients with heart failure (HF). This comprehensive literature review evaluated the current evidence on the COP and its potential as an independent risk factor for cardiovascular disease and mortality. The COP has been identified as a predictor of all-cause and cardiovascular mortality, with elevated values being significantly associated with an increased risk. Studies have demonstrated that higher COP values correlate with greater mortality risk independent of traditional risk factors, with significant sex-based differences. Evidence suggests that COP values greater than 26 significantly influence mortality rates and lead to a worse prognosis in patients with HF. For example, individuals with a COP > 30 had an approximately six-fold higher mortality risk (17.1%) than those with a COP < 22, and the combination of a high COP (>30) + low VO2max leads to a significant increase in the risks of adverse effects (30.9%). This underscores the importance of the COP in the clinical management and risk stratification of HF patients. While the COP shows promise as a valuable submaximal marker with significant prognostic implications, further research is needed to establish its superiority over other established prognostic markers and elucidate the underlying mechanisms linking the COP to health outcomes. Nonetheless, the ability of the COP to predict mortality and enhance risk stratification in diverse populations makes it a promising tool in clinical practice.